2005
DOI: 10.1136/tc.2004.008839
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hospitality workers’ exposure to secondhand smoke following the implementation of New York’s smoke-free law

Abstract: Objective: To assess the impact on hospitality workers' exposure to secondhand smoke of New York's smoke-free law that prohibits smoking in all places of employment, including restaurants, bars, and bowling facilities. Design: Pre-post longitudinal follow up design. Settings: Restaurants, bars, and bowling facilities in New York State. Subjects: At baseline, 104 non-smoking workers in restaurants, bars, and bowling facilities were recruited with newspaper ads, flyers, and radio announcements. Of these, 68 comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
1
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(126 citation statements)
references
References 13 publications
6
111
1
8
Order By: Relevance
“…Previous studies have mainly used indirect assessment methods of exposure to environmental tobacco smoke, including subjective reports (9), particle sampling, or exhaled carbon monoxide (43). The sampling of cotinine from bodily fluids is a more direct measurement of environmental tobacco smoke, and it was also used (8,9). However, urinary cotinine is influenced by individual physiological (respiration, absorption, metabolism, and excretion), temporal (exposure duration), and physical (exposure concentration) parameters (27).…”
Section: Larsson Et Almentioning
confidence: 99%
“…Previous studies have mainly used indirect assessment methods of exposure to environmental tobacco smoke, including subjective reports (9), particle sampling, or exhaled carbon monoxide (43). The sampling of cotinine from bodily fluids is a more direct measurement of environmental tobacco smoke, and it was also used (8,9). However, urinary cotinine is influenced by individual physiological (respiration, absorption, metabolism, and excretion), temporal (exposure duration), and physical (exposure concentration) parameters (27).…”
Section: Larsson Et Almentioning
confidence: 99%
“…A cross-sectional study of 53 hospitality venues in 7 major cities across the USA showed 82% less indoor air pollution in the locations subject to smoke-free air laws, even though compliance with the laws was less than 100% [12]. In the months after New York State's smoke-free law took effect, hospitality workers experienced large decreases in cotinine, a biomarker for nicotine exposure, and were less likely to report adverse symptoms such as wheezing, cough, and shortness of breath [13]. Ten months after Scotland's smoke-free law took effect, admissions for acute coronary syndrome decreased by 17% compared to a 4% decrease in neighboring England, which did not have a smoke-free law in effect at the time [14].…”
mentioning
confidence: 99%
“…Multiple studies have documented the positive short-term impact of smoke-free legislation in the improvement of self-reported sensory and respiratory symptoms as well as of lung function measures (Allwright et al, 2005;Ayres et al, 2009;Eagan, Hetland, & Aaro, 2006;Eisner, Smith, & Blanc, 1998;Farrelly et al, 2005;Lai et al, 2011;Larsson, Boethius, Axelsson, & Montgomery, 2008;Menzies et al, 2006;Pearson, Windsor, El-Mohandes, & Perry, 2009;Schoj et al, 2010;Skogstad et al, 2006;Wakefield, Cameron, Inglis, Letcher, & Durkin, 2005). On the contrary, incomplete bans do not improve workers' respiratory health (Fernandez et al, 2009).…”
Section: Respiratory and Sensory Symptomsmentioning
confidence: 99%